Menin‐regulated Pbk controls high fat diet‐induced compensatory beta cell proliferation. Issue 5 (6th April 2021) - Ma, Jian; Xing, Bowen; Cao, Yan; He, Xin; Bennett, Kate E; Tong, Chao; An, Chiying; Hojnacki, Taylor; Feng, Zijie; Deng, Sunbin; Ling, Sunbin; Xie, Gengchen; et al.
Abstract: Pancreatic beta cells undergo compensatory proliferation in the early phase of type 2 diabetes. While pathways such as FoxM1 are involved in regulating compensatory beta cell proliferation, given the lack of therapeutics effectively targeting beta cell proliferation, other targetable pathways need to be identified. Herein, we show that Pbk, a serine/threonine protein kinase, is essential for high fat diet (HFD)‐induced beta cell proliferation in vivo using a Pbk kinase deficiency knock‐in mouse model. Mechanistically, JunD recruits menin and HDAC3 complex to the Pbk promoter to reduce histone H3 acetylation, leading to epigenetic repression of Pbk expression. Moreover, menin inhibitor (MI) disrupts the menin–JunD interaction and augments Pbk transcription. Importantly, MI administration increases beta cell proliferation, ameliorating hyperglycemia, and impaired glucose tolerance (IGT) in HFD‐induced diabetic mice. Notably, Pbk is required for the MI‐induced beta cell proliferation and improvement of IGT. Together, these results demonstrate the repressive role of the menin/JunD/Pbk axis in regulating HFD‐induced compensatory beta cell proliferation and pharmacologically regulating this axis may serve as a novel strategy for type 2 diabetes therapy. Synopsis: Pancreatic beta cells undergo compensatory proliferation in the early phase of type 2 diabetes. Understanding the mechanism and regulation of compensatory beta cell proliferation may allow for improved treatment options for diabetes. Herein we elucidated that the menin/JunD/Pbk axis is important in compensatory beta‐cell proliferation. Pbk is crucial for regulating compensatory pancreatic beta cell proliferation of high fat diet (HFD) fed mice. Menin and HDAC3 complex were recruited by JunD to epigenetically repress Pbk expression. Menin‐JunD interaction was interrupted by small molecule menin inhibitors (MIs), leading to upregulating of Pbk gene expression, beta cell proliferation, and improved glucose tolerance in diet‐induced obese and diabetic mice. Pbk is required for MI‐induced beta cell proliferation and improved glucose tolerance in HFD‐induced diabetic mice. Abstract : Pancreatic beta cells undergo compensatory proliferation in the early phase of type 2 diabetes. Understanding the mechanism and regulation of compensatory beta cell proliferation may allow for improved treatment options for diabetes. Herein we elucidated that the menin/JunD/Pbk axis is important in compensatory beta‐cell proliferation.